2002
DOI: 10.1111/1468-5957.00455
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Asset Sales: Evidence of Earnings Management?

Abstract: This paper presents empirical evidence from a sample of publicly traded Singaporean firms on the question: to what extent do firms manage earnings through the timing of asset sales? Previous studies have focused on accounting motives behind asset sales, ignoring the need to also consider economic motives. Some empirical evidence is provided to support the hypothesis that managers of firms with decreasing net earnings-per-share smooth earnings upwards using asset sales. Copyright Blackwell Publishers Ltd 2002.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
1
15
1
1
Order By: Relevance
“…In doing so, we include a variable controlling for client size (FirmSize) in Model 1, as prior research has shown that auditors act more conservatively when auditing larger clients (e.g., Reynolds & Francis, 2000). Furthermore, we add variables that control for financial condition (Loss t-1 , CFO, and Leverage) and growth (SalesGrowth, PPEGrowth, and BTM) to the model, as highgrowth companies and companies that are in a weak financial condition are more likely to manage earnings to a greater extent (Matsumoto, 2002;Poitras, Wilkins, & Kwan, 2002). Finally, we also include a variable capturing the issuance of equity (Issuance) in our audit quality model.…”
Section: Company Characteristicsmentioning
confidence: 99%
“…In doing so, we include a variable controlling for client size (FirmSize) in Model 1, as prior research has shown that auditors act more conservatively when auditing larger clients (e.g., Reynolds & Francis, 2000). Furthermore, we add variables that control for financial condition (Loss t-1 , CFO, and Leverage) and growth (SalesGrowth, PPEGrowth, and BTM) to the model, as highgrowth companies and companies that are in a weak financial condition are more likely to manage earnings to a greater extent (Matsumoto, 2002;Poitras, Wilkins, & Kwan, 2002). Finally, we also include a variable capturing the issuance of equity (Issuance) in our audit quality model.…”
Section: Company Characteristicsmentioning
confidence: 99%
“… The components of non‐operating income, such as profits from the sale of fixed assets or investments, have been shown to be tools of earnings management in the U.S. (Bartov, ) and other countries, such as Singapore (Poitras et al., ). …”
mentioning
confidence: 99%
“…Inoue and Thomas (1996), Poitras et al (2002) and Herrmann et al (2003) indicate a positive correlation between firm size and AS. Following Herrmann et al (2003), the log of total assets (SIZE) and prior AS (AS t−1 , found to be positively correlated with AS in a current quarter) are included as the control variables.…”
Section: Control Variables To As and Asdummy Equationsmentioning
confidence: 97%